Tinjauan Hukum Islam terhadap Transaksi Jual Beli Rumah Via Katalog di PT. Bali Karisma Pratama - Ummal Khoiriyah (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2017)
Property and housing is national and international issues were should fully appreciated by the government. It becomes a primary needs for every citizen. It is certainly can not be separated from mualamah itself. Especially buying and selling houses can take place not only between individuals with a particular company but also between individuals. This study includes the provisions set by the seller to the buyer in that process of transaction in the form of buying and selling property and housing using a catalog in the PT. Bali Karisma Pratama, which is analyzed using Islamic law (al-Qur’an, Hadith, and the opinion Ulama ‘Expert Fiqh).